Diffusion Affine Projection Sign Algorithm based on QR-Decomposition - Suchada Sitjongsataporn; Sethakarn Prongnuch; Theerayod Wiangtong (My University, 2021)
In this paper, an Adapt-Then-Combine diffusion strategy on affine projection sign algorithm is presented. Based on the QR-decomposition method, the modified inverse autocorrelation matrix is shortly brief to decrease the computational complexity. The Adapt-Then-Combine diffusion strategy is applied on the low complexity of sign algorithm version of inverse square-root affine projection algorithm including with the adaptation and combination steps. By applying an idea of diffusion adaptation algorithm, we derive a diffused version of an affine projection sign algorithm based on QR-Decomposition, denoted as DiQR-APSA. Experimental results show that the proposed DiQR-APSA can achieve the good performance in comparison with the standard affine projection sign algorithm.
Keywords: Advanced Adaptive Filtering Techniques; Blind Source Separation Techniques; Speech and Audio Processing